Respiratory status in dairy farmers in France; cross sectional and longitudinal analyses. Issue 11 (22nd October 2003) - Chaudemanche, H; Monnet, E; Westeel, V; Pernet, D; Dubiez, A; Perrin, C; Laplante, J-J; Depierre, A; Dalphin, J-C
Abstract : Aims: To compare respiratory status in dairy farmers with that of non-farming controls. Methods: Longitudinal study in the Doubs (France). From a cohort constituted in 1994 (T1), 215 (81.1%) dairy farmers and 110 (73.8%) controls were reevaluated in 1999 (T2). The protocol comprised a medical and occupational questionnaire, spirometric tests at both evaluations, allergological tests at T1, and a non-invasive measure of blood oxygen saturation (Spo 2 ) at T2. Results: In 1999 analyses, the prevalence of chronic bronchitis was higher (p = 0.013), and FEV1 /VC (p < 0.025) and Spo 2 (−0.7%, p < 0.01) lower in dairy farmers than in controls. In a multiple linear regression model, farming, age, and smoking were significantly and inversely correlated with Spo 2 . In the whole population, the mean annual decline in FEV1 and FEV1 /VC was −13.4 ml and −0.30%, respectively. Farming was associated with an accelerated decline in FEV1 /VC (p < 0.025) after adjustment for covariates. No relation between allergy and respiratory function changes was observed, except for FEF25–75 . Conclusions: This prospective study shows that dairy farming is associated with an excess of chronic bronchitis, with a moderate degree of bronchial obstruction and a mild decrease in Spo 2 .